2021
DOI: 10.3390/app11094281
|View full text |Cite
|
Sign up to set email alerts
|

Mining Textual and Imagery Instagram Data during the COVID-19 Pandemic

Abstract: Instagram is perhaps the most rapidly gaining in popularity of photo and video sharing social networking applications. It has been widely adopted by both end-users and organizations, posting their personal experiences or expressing their opinion during significant events and periods of crises, such as the ongoing COVID-19 pandemic and the search for effective vaccine treatment. We identify the three major companies involved in vaccine research and extract their Instagram posts, after vaccination has started, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…This way, they were able to take the sentiment analysis a step further and explain some of the changes in the data. The three leading companies who were involved in research on vaccines were identified as Pfizer, AstraZeneca, and Johnson and Johnson [ 11 ]; researchers extracted their Instagram posts from the start of vaccination and received data from users using their own hashtags. The companies' qualitative variations in manuscripts and visual characteristics (i.e., image categorization by transfer learning) are initially presented in this research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This way, they were able to take the sentiment analysis a step further and explain some of the changes in the data. The three leading companies who were involved in research on vaccines were identified as Pfizer, AstraZeneca, and Johnson and Johnson [ 11 ]; researchers extracted their Instagram posts from the start of vaccination and received data from users using their own hashtags. The companies' qualitative variations in manuscripts and visual characteristics (i.e., image categorization by transfer learning) are initially presented in this research.…”
Section: Introductionmentioning
confidence: 99%
“…In this way they were able to take the sentimental analysis a step further and explain some of the changes in the data. The three leading companies are identified: Pfizer, AstraZeneca and Johnson and Johnson, who are involved in research on vaccines and researchers [11] extract their Instagram posts from the start of vaccination and who receive data from users using their own hashtags. The company qualitative variations on manuscripts and visual characteristics, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…AstraZeneca had an Instagram account longer than the other two; had the most posts and the highest rate of posting. However, it has the lowest number of followers (Amanatidis et al, 2021).…”
Section: Subtheme: Qualitative Researchmentioning
confidence: 99%
“…The other huge social platform of our time is undoubtedly Instagram. In [21], the authors examined the Instagram entries of three major vaccine manufacturers. In the comments under the posts of these companies, the users' intention to comment was mainly to make general statements, communicate facts, and share experiences, which in this context, meant their post-vaccination experience.…”
Section: Sentiment Analysis In Covid-19mentioning
confidence: 99%